Alkali promoted tungsten carbide as a selective catalyst for the reverse water gas shift reaction. Issue 35 (January 2020) - Morse, James R.; Juneau, Mitchell; Baldwin, Jeffery W.; Porosoff, Marc D.; Willauer, Heather D.
Graphical abstract: Highlights: WC was found to be an effective catalyst for the reverse water gas shift reaction. Alkali addition alters the structural and electronic properties of WC. Alkali addition greatly improves the selectivity of WC for this reaction. WC and alkali-WC demonstrate long term catalytic stability. Abstract: The conversion of CO2 to CO via the reverse water gas shift (RWGS) reaction is often envisioned as the first step in the large scale transformation of CO2 into value added hydrocarbons. Accordingly, low-cost and highly selective RWGS catalysts are desirable materials for sustainable CO2 utilization. Here, we describe synthesis, characterization and performance evaluation of alkali metal promoted tungsten carbide (WC) RWGS catalysts, supported on porous γ-Al2 O3 . Scanning electron microscopy reveals significant differences in the morphology of the catalysts, while X-ray photoelectron spectroscopy indicates a greater extent of carburization of the alkali-promoted catalysts, suggesting that alkali metals act as structural and electronic promoters, respectively. Performance data for the RWGS reaction at 300 and 350 °C shows all catalysts are active, with the alkali promoted catalysts demonstrating improved CO selectivity. Of the catalysts tested, the highest CO yield is achieved using K-promoted WC, demonstrating K-WC/γ-Al2 O3 is a low-cost, active and selective RWGS catalyst.